Synthesis of novel methyl jasmonate derivatives and evaluation of their biological activity in various cancer cell lines - Onur Sucu, Bilgesu; Savluğ İpek, Özgecan; Özdatlı Kurtuluş, Şükran; Yazıcı, Büşra Emine; Karakaş, Nihal; Güzel, Mustafa (Academic Press Inc Elsevier Science, 2019)
Warburg hypothesized that the energy consumption of cancer cells is different than the normal cells. When compared to normal conditions, cancer cells do not undergo tricarboxylic acid (TCA) cycle therefore resulting in more lactate in the cells. Glycolysis pathway is a way of cancer cells to provide energy. The first step in glycolysis is the phosphorylation of glucose to glucose-6-phosphate. This reaction is catalyzed by the hexokinase-II enzyme (HK-II) which is known to be overexpressed in tumor cells. The feeding of cancer cells can be prevented by inhibiting the hexokinase-II enzyme in the first step of aerobic glycolysis. In literature, Methyl Jasmonate (MJ) is known as a Hexokinase-II inhibitor since it disposes VDAC and HK-II interaction on mitochondrial membrane. In our study, we aimed to increase the activity by synthesizing the novel MJ analogues with appropriate modifications. Here we report Hexokinase-2 enzyme and cell viability study results in different cancer cells. Based on the three different cancer cell lines we investigated, our novel MJ analogues proved to be more potent than the original molecule. Thus this research may provide more efficacious/ novel HK-II inhibitors and may shed light to develop new anti-cancer agents.
Keywords: Cancer Therapy; Aerobic Glycolysis; Warburg Effect; Hexokinase-II Inhibition; Methyl Jasmonate; Novel Drug Discovery and Development